Fiber optic humidity sensor based on silk fibroin interference films - Opilski, Zbigniew; Procek, Marcin; Aznar-Cervantes, Salvador; Cenis, Jose; Munoz, Xavier (Photonics Letters of Poland, 2020)
The article presents an inexpensive and simple method of fiber optic interference relative humidity (RH) sensors based on silk fibroin (SF) films. The sensors were made on standard multimode telecommunications optical fibers using dip-coating method and examined using broadband light sources. The measuring stand at which the basic sensor parameters were measured and the measured parameters were presented. Full Text: PDF References Y.-G. Han, "Relative Humidity Sensors Based on Microfiber Knot Resonators—A Review", Sensors, 19(23), 5196 (2019) CrossRef L.D. Koh, Y. Cheng, C. P. Teng, Y. W. Khin, X. J. Loh, S. Y. Tee, et al., "Structures, mechanical properties and applications of silk fibroin materials", Prog. Polim. Sci. 46, 86-110 (2015) CrossRef H. Tao, D. L. Kaplan, F. G. Omenetto, "Silk Materials – A Road to Sustainable High Technology", Adv. Mater., 24, 2824-2837 (2012), CrossRef Q. Li, N. Qi, Y. Peng, Y. Zhang, L. Shi, X. Zhang, et al., "Sub-micron silk fibroin film with high humidity sensibility through color changing", RSC Adv. 7(29), 17889-17897 (2017) CrossRef S.K. Hwan, H.C. Sung, B. Roy, S. Kim, Y.H. Ahn, "Humidity sensing using THz metamaterial with silk protein fibroin", Opt. Express 26(26), 33575-33581 (2018) CrossRef M. Procek, Z. Opilski, A. M. Maqueda, X. M. Berbel, S. D. Aznar-Cervantes, J. L. Cenis, C. D. Horna, "Silk fibroin thin films for optical humidity sensing", Proc. SPIE , 11204, 0277-786X, (2019). CrossRef Y. Luo, Y. Pei, X. Feng, B. Lu, L. Wang, "Silk fibroin based transparent and wearable humidity sensor for ultra-sensitive respiration monitoring", Mater. Lett., 260, 126945 (2020) CrossRef E. Maciak, "Low-Coherence Interferometric Fiber Optic Sensor for Humidity Monitoring Based on Nafion® Thin Film†", Sensors 19(3), 629 (2019) CrossRef